Does Human Capital Improve Health Care Agility through Health Care Supply Chain Performance? Moderating Role of Technical Orientation - Somdech Rungsrisawat; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
Supply chain is not just confined to manufacturing or production-oriented industries but its implications are also there in healthcare sector. Such healthcare supply chain can work even better with proper care on human capital side. With an increase or betterment in human capital, agility of the sector also gets affected. In this study, author has checked the impact of human capital on health care agility in Thailand’s health care sector along with analyzing the mediating role of healthcare supply chain performance in given relationship. Moreover, moderating role of technological orientation was also assessed in relationship between human capital and healthcare supply chain performance. Data has been collected from various hospitals of Thailand and questionnaires were distributed among administrative staff of those hospitals. Responses were then analyzed on SPSS and AMOS through applying various screening and structural equation modeling test. Results have indicated that human capital significantly enhances agility in healthcare sector and healthcare supply chain performance also significantly mediates in this relationship. Implications of this study are mostly focusing on service sector that it can improve its agility through better human capital and with increases supply chain performance.